2021
DOI: 10.3390/ijerph18116124
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Integrated Education to Reduce Postoperative Nausea, Vomiting, and Dizziness after Abdominal Surgery under General Anesthesia

Abstract: This study presents an anticipatory integrated education program for nausea, vomiting, and dizziness prevention (anti-NVD education program) for patients undergoing abdominal surgery under general anesthesia. The anti-NVD education program for nephrectomy patients consisted of the following: the causes of postoperative nausea, vomiting, and dizziness; effective deep breathing and how to use an inspirometer; postoperative nausea and vomiting; effective methods of patient-controlled analgesia; and the stepwise s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Due to different diagnostic criteria, the incidence of gastroparesis reported in some literature is 0.3% to 10% [ 2 ]. The incidence of gastroparesis after gastrectomy can be as high as 4.7% [ 3 ]. The etiology of gastroparesis after abdominal surgery is not yet clear, which may be related to the following factors: (1) whether there is gastric outflow tract obstruction before surgery: generally, patients with gastric outflow tract obstruction before surgery are more likely to develop postoperative gastric outflow tract obstruction than those without obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Due to different diagnostic criteria, the incidence of gastroparesis reported in some literature is 0.3% to 10% [ 2 ]. The incidence of gastroparesis after gastrectomy can be as high as 4.7% [ 3 ]. The etiology of gastroparesis after abdominal surgery is not yet clear, which may be related to the following factors: (1) whether there is gastric outflow tract obstruction before surgery: generally, patients with gastric outflow tract obstruction before surgery are more likely to develop postoperative gastric outflow tract obstruction than those without obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn may contribute to a decrease in pain severity. Studies have reported that patients with preoperative anxiety who had received web‐based information prior to surgery concerning what to expect and how to manage it experienced fewer postoperative difficulties in terms of symptom development, pain (Bisbey et al, 2017), nausea, and vomiting (Seok et al, 2021). We also believe that the lower pain levels in our intervention group compared with the control group were associated with anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show that when patients are prepared with web‐based information prior to surgery, their anxiety levels decrease (Kim et al, 2019; Rostami et al, 2021), patient safety improves (Yin et al, 2015), and patient satisfaction increases (van Eck et al, 2018). Web‐based patient education during surgery is also effective in preventing nausea, vomiting, and dizziness (Seok et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of pain has been the focus of medicine for many years and has been approached in different ways by physicians to manage pain during and after surgery (15,16). However, recent approaches focussed on non-invasive therapies such as deep breathing exercises (6) and integrated educational programs (17) to alleviate post-operative non-pain symptoms after surgery. Here we studied the effect of the MPMP intervention on the post-operative discomfort factors in patients undergoing abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%